2018
DOI: 10.3390/ma11101969
|View full text |Cite
|
Sign up to set email alerts
|

A Granite Bed Storage for a Small Solar Dryer

Abstract: The article presents the concept of a high-temperature solar dryer with an internal bed storage. Granite was selected as the material for filling the bed storage, and an emphasis was put on its versatile use and favourable thermal and mechanical properties. Experimental tests were carried out for the charging process of the bed storage, which was filled with granite spheres with three different diameters. The influence of the sphere’s diameter on the charging and discharging process of the bed storage was anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Previous experimental studies, which concerned a granite bed storage and which were carried out by the author of this paper, showed a different nature of the storage process in relation to the shape of the tested material [14]. Different characteristics of the working medium's outlet temperature from the heat storage were obtained for the same testing conditions.…”
Section: Introductionmentioning
confidence: 59%
“…Previous experimental studies, which concerned a granite bed storage and which were carried out by the author of this paper, showed a different nature of the storage process in relation to the shape of the tested material [14]. Different characteristics of the working medium's outlet temperature from the heat storage were obtained for the same testing conditions.…”
Section: Introductionmentioning
confidence: 59%
“…The specific heat of this material is equal to 780 J/(kg•K), which makes it attractive in terms of heat storage. It is also resistant to working in high temperatures of even several hundred degrees Celsius [19].…”
Section: Methodsmentioning
confidence: 99%
“…V air . The design of the Hartley experiment, which was described in detail in [19,20], was selected for the investigation. It enabled the tests to be carried out for three input factors at three levels of variation.…”
Section: Test Stand and Experiments Planmentioning
confidence: 99%
“…According to the authors, all the evaluated systems presented high performance and stable output temperature suitable for drying process up to 60 °C. Nems et al (2018) presented a concept of vertical flow high temperature solar dryer with granite balls in the bed of the dryer acting as thermal storage. Experimental results have shown that granite can prolong the operation of the dryer in two hours.…”
Section: State Of the Artmentioning
confidence: 99%